'Testing volatility on the Trinidad and Tobago Stock Exchange' - Nicholls, Shelton ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Examines the risk-return profiles on the Trinidad and Tobago Stock Exchange and the volatility of returns of various portfolios on the market.